'Surface Contrast' NMR Reveals Non‐innocent Role of Support in Pd/CeO2 Catalyzed Phenol Hydrogenation. Issue 16 (24th June 2020) - Egner, Timothy K.; Naik, Pranjali; An, Yeongseo; Venkatesh, Amrit; Rossini, Aaron J.; Slowing, Igor I.; Venditti, Vincenzo
Abstract: Ceria (CeO2 )‐supported metals are widely used as catalysts because of their exceptional redox properties. Here, we use surface contrast NMR methods to investigate the hydrogenation of phenol by Pd supported on ceria nanoparticles. We show that the rigid and planar binding of phenol to Pd is mediated by a weak and highly mobile association of the small molecule to ceria. Interestingly, while addition of phosphate to the mixture does not perturb the adsorption of phenol on Pd, it destabilizes its interaction with ceria and proportionally decreases the rate of catalytic conversion. Our data provide strong experimental evidence that weak interactions between adsorbate and ceria are catalytically competent and explain the exceptional performance of Pd/CeO2 for reductive conversions under mild reaction conditions. Abstract : SC‐NMR was sed to investigate the kinetics and thermodynamics of PhOH adsorption on the surface of a Pd/CeO2 catalyst. Adsorption to Pd is mediated by a weak PhOH‐CeO2 adduct in which the small molecule is hydrogen bonded to the ceria support. Selective perturbation of the interaction between PhOH and support disrupts the activity of the catalyst, suggesting that hydrogen bonding of PhOH to ceria is competent for catalysis.